Characteristics of peptide and major histocompatibility complex class I/beta 2-microglobulin binding to the transporters associated with antigen processing (TAP1 and TAP2). - Androlewicz, M J (1994)
The transporter proteins associated with antigen processing (TAP proteins) transport antigenic peptides across the endoplasmic reticulum membrane where they can assemble with newly synthesized major histocompatibility complex (MHC) class I/beta 2-microglobulin (beta 2m) dimers. We have shown previously that TAP possesses a peptide-recognition site with broad specificity and that MHC class I/beta 2m dimers physically associate with TAP. Here, we further characterize the nature of the peptide-binding site on TAP, and the site of interaction of TAP with MHC class I/beta 2m dimers. TAP photoaffinity labeling experiments revealed that both TAP1 and TAP2 are photolabeled by two distinct photopeptide analogues, suggesting that elements of both TAP1 and TAP2 compose the peptide-recognition site. TAP photolabeling analysis on transfectant cell lines that express TAP1 and TAP2 both individually and together revealed that efficient formation of the peptide-binding site occurs only when TAP1 and TAP2 are coexpressed, which correlates with the finding that peptide translocation via TAP occurs only in the presence of both TAP1 and TAP2. These data strongly support the notion that TAP functions as a heterodimer. MHC class I/beta 2m dimers were shown to associate with individual TAP1 chains but were not detectable with individual TAP2 chains. This result suggests that the site of interaction for MHC class I/beta 2m dimers with TAP is on TAP1.